2022
DOI: 10.1002/jcph.2140
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multiple Concomitant CYP3A Inhibitors on Venetoclax Pharmacokinetics: A PBPK and Population PK‐Informed Analysis

Abstract: Venetoclax is an approved, orally bioavailable, B-cell lymphoma type 2 (BCL-2) inhibitor that is primarily metabolized by cytochrome P450 3A (CYP3A). Polypharmacy is common in patients undergoing treatment for hematological malignancies such as acute myeloid leukemia or chronic lymphocytic leukemia, and although venetoclax exposure has been well characterized with 1 concomitant CYP3A inhibitor, complex drug-drug interactions (DDIs) involving more than 1 inhibitor have not been systematically evaluated. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Owing to an already large reduction (85%) in clearance caused by strong CYP3A inhibitors, additional CYP3A inhibitors are unlikely to add to the effect. Interestingly, a recent study published using a physiologically based PK approach had come to a similar conclusion that when combining 1 strong CYP3A inhibitor with additional competitive CYP3A inhibitors, no further effect can be observed beyond a single strong inhibitor alone 32 …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Owing to an already large reduction (85%) in clearance caused by strong CYP3A inhibitors, additional CYP3A inhibitors are unlikely to add to the effect. Interestingly, a recent study published using a physiologically based PK approach had come to a similar conclusion that when combining 1 strong CYP3A inhibitor with additional competitive CYP3A inhibitors, no further effect can be observed beyond a single strong inhibitor alone 32 …”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, a recent study published using a physiologically based PK approach had come to a similar conclusion that when combining 1 strong CYP3A inhibitor with additional competitive CYP3A inhibitors, no further effect can be observed beyond a single strong inhibitor alone. 32 The expanded and improved population PK model successfully characterized venetoclax plasma concentration across multiple patient populations and healthy volunteers. Comprehensive covariate analyses validated previously reported clinically relevant factors affecting venetoclax PK, supporting the recommendation in the prescribing information to administer venetoclax with food and reduce venetoclax dosage when coadministered with moderate and strong CYP3A inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…31,50 This supports that the recommended dose adjustment of venetoclax when administered in combination with more than one strong CYP3A inhibitor should be identical to that prescribed for a single strong CYP3A inhibitor. 50…”
Section: Effect Of Cyp3a Inhibitors On Venetoclaxmentioning
confidence: 72%
“…A common issue with patients with hematological malignancies is the need for multiple therapies to address comorbidities or side effects from cancer treatments. Using PBPK and popPK to investigate whether additional dose adjustments were needed in patients taking multiple strong CYP3A inhibitors concomitantly, it was found that venetoclax exposures were similar to that of just taking one strong CYP3A inhibitor 31,50 . This supports that the recommended dose adjustment of venetoclax when administered in combination with more than one strong CYP3A inhibitor should be identical to that prescribed for a single strong CYP3A inhibitor 50 …”
Section: Drug–drug Interactionsmentioning
confidence: 82%
“…A summary of the included analyses is shown in Table 1. Among the six analyses included, a median (range) of 274 (73-3016) patients were used for the development of the PPK model, with five analyses 11,16,18,19,22 involving more than 200 subjects. All analyses were based on clinical trials, and three analyses did not state NCT numbers.…”
Section: Study Characteristicsmentioning
confidence: 99%